Modeling of Marine Asynchronous Shaft Generator and Simulation of Subsynchronization State. (3rd November 2020) - Langtao, Yan; Jiawan, Tan; Yusheng, Liu; Hui, Yang
Abstract : The new type of marine asynchronous shaft generator has the advantages of adjustable excitation and power factor, compared to the traditional synchronous shaft generator, and has been widely used. However, the traditional synchronous shaft generator simulation system is still used in domestic ship power station simulators, which seriously restricts the renewal of crew training. In order to overcome the shortage of the simulation system of doubly fed shaft generator for ship power plant simulator, in this paper, the mathematical model of marine doubly fed shaft system is established for the first time, according to the characteristics of doubly fed machine and marine shaft generator. This paper realizes power decoupling by stator flux orientation and simulates and analyses the asynchronous shaft generator under subsynchronous working conditions. The changing trend of each physical quantity in the simulation waveform meets the mathematical relationships of the actual physical quantity, which proves the correctness of the mathematical model and lays a theoretical foundation for the development of the simulation system of asynchronous shaft generator.